2008
DOI: 10.1016/j.yhbeh.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Activational effects of estradiol and dihydrotestosterone on social recognition and the arginine-vasopressin immunoreactive system in male mice lacking a functional aromatase gene

Abstract: In rodents, parts of the arginine-vasopressin (AVP) neuronal system are sexually dimorphic with males having more AVP-immunoreactive cells/fibers than females. This neuropeptide neuronal system is highly sensitive to steroids and has been proposed to play an important role in the processing of olfactory cues critical to the establishment of a social memory. We demonstrate here that gonadally intact male aromatase knockout (ArKO) mice, which cannot aromatize androgens into estrogens due to a targeted mutation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 35 publications
6
41
1
Order By: Relevance
“…This is in agreement with the findings that non-copulating rats, while having similar testosterone levels as copulating rats, display reduced neuronal aromatase (Ar) activity and levels of ERα [131,132]. ArKO mice have a similar social and sexual phenotype as the ERαKO [128,133] further supporting the idea of aromatase and ERα dependent responses.…”
Section: Estrogen Receptors and Male Risk Takingsupporting
confidence: 89%
“…This is in agreement with the findings that non-copulating rats, while having similar testosterone levels as copulating rats, display reduced neuronal aromatase (Ar) activity and levels of ERα [131,132]. ArKO mice have a similar social and sexual phenotype as the ERαKO [128,133] further supporting the idea of aromatase and ERα dependent responses.…”
Section: Estrogen Receptors and Male Risk Takingsupporting
confidence: 89%
“…Male aromatase KO mice display impairments in spatial reference memory (Martin et al, 2003), whereas severe deficits in social memory were seen in both gonadally intact and castrated male aromatase KO mice (Pierman et al, 2008). Interestingly, when gonadally intact or castrated male aromatase null mice were treated with estradiol benzoate, in association with dihydrotestosterone propionate, a recovery in social recognition was observed (Pierman et al, 2008). Collectively, these studies indicate that 17b-estradiol contributes to cognition in male rodents.…”
Section: B Studies Using Rodent Modelsmentioning
confidence: 78%
“…Several strains of aromatase KO mice have been produced (Fisher et al, 1998;Honda et al, 1998;Toda et al, 2001), resulting in mice that are estrogen deficient and hyperandrogenic. Male aromatase KO mice display impairments in spatial reference memory (Martin et al, 2003), whereas severe deficits in social memory were seen in both gonadally intact and castrated male aromatase KO mice (Pierman et al, 2008). Interestingly, when gonadally intact or castrated male aromatase null mice were treated with estradiol benzoate, in association with dihydrotestosterone propionate, a recovery in social recognition was observed (Pierman et al, 2008).…”
Section: B Studies Using Rodent Modelsmentioning
confidence: 99%
“…However, the most compelling evidence suggesting the HPG axis is crucial for maternal behavior comes from studies of mice that lack either aromatase (Ogawa et al, 1998; Spiteri et al, 2010a, 2010b) or estrogen receptor (ER) alpha (Pierman et al, 2008), which are discussed in the genetics section.…”
Section: Biological Determinants Of Motivation In a Social Contextmentioning
confidence: 99%
“…Concerning the HPG axis, gene knockout studies have found that mice lacking a key enzyme involved in estrogen synthesis, aromatase, display deficits in social recognition (essential for establishing the mother-infant bond) and AVP activation (Pierman et al, 2008). They also report that the exogenous administration of estrogen recovers social recognition and AVP activation.…”
Section: Genetic and Epigenetic Influencesmentioning
confidence: 99%